INTERPRETATION IN UZBEK FEATURE FILMS ON FRONTLINE COURAGE - Aziz A. Matyakubov (International Scientific and Current Research Conferences, 2022)
The article focuses on Uzbek feature films that reflect the courage of the Uzbek people on the front lines. The analysis summarizes the directions and artistic interpretations of the courage of the Uzbeks on the front lines.